How Digital Content Quality and Online Promotion Influence Online Purchase Decisions Through Consumer trust - Sri Rahayu; Muhammad Apriliansyah Rahmadhani; M. Agus Kurniawan; Winata Nugraha; Uci Suriani (Information Technology and Science (ITScience), 2026)
The need to better understand the elements influencing consumers' online purchasing decisions has arisen as a result of the intense competition among online merchants brought about by the rapid expansion of digital business. Although earlier research has emphasized the significance of promotional tactics and high-quality digital material, empirical results about their relative efficacy and the function of trust in online buying situations are still contradictory. With customer trust acting as a mediating variable, this study attempts to investigate the impact of digital content quality and online promotion on online purchase decisions. Using survey information gathered from 150 online shoppers who had made purchases via digital platforms, a quantitative study methodology was used. Partial Least Squares–Structural Equation Modeling (PLS-SEM) was used to examine the data in order to evaluate the measurement and structural models. The findings show that while consumer trust has a substantial impact on online purchase decisions, online promotion has a big beneficial impact on both. On the other hand, neither customer trust nor online purchase decisions are significantly impacted by the quality of digital material. These results imply that promotional incentives and trust-building strategies are more important than content quality alone in influencing consumer purchasing behavior in fiercely competitive digital marketplaces. Practically speaking, the findings suggest that in order to improve purchase outcomes, digital companies should prioritize clear and appealing promotional techniques while also building customer trust.